Solvent-based recovery of acrylate polymer from display film waste - Lee, Nahyeon; Ahn, Byungmin; Lee, Jechan (Energy and Environment, 2024)
Acrylate polymer is widely used to manufacture display films as an adhesive. Improper disposal of acrylate polymer-containing display film waste (a kind of E-waste) may cause serious environmental problems. As an effort to develop a display film waste treatment strategy, this study applied a solvent-based method to recover acrylate polymer from display film waste. The solubility of acrylate polymer (e.g. poly(tert-butyl acrylate)) in 18 different organic solvents was calculated using Hansen solubility parameters. As a result, 2-butanol and methyl acetate were chosen as organic solvents for the acrylate polymer recovery from the display film waste. Effects of various recovery parameters (e.g. temperature, time, and stirring speed) on the recovery of acrylate polymer in five different solvent systems consisting of 2-butanol and methyl acetate (2-butanol, methyl acetate, 1:1 mixture, 1:2 mixture, and 2:1 mixture) were explored. 2-Butanol was found to be a better solvent than any others because it is more hydrophobic than methyl acetate. The recovery condition at which the highest acrylate polymer recovery yield in 2-butanol was obtained was T = 30 °C, t = 1 h, and stirring speed of 250 r/min, reaching 8.28 wt%. This study would help to develop an E-waste recycling method that can be recovering value-added products from E-waste.
Keywords: 2-butanol; Acrylate polymers; E-wastes; Environmental problems; Methyl acetates; Plastics recycling; Plastics waste; Solvent based; Solvent-based methods; Stirring speed; E-waste; organic solvent; plastic recycling; Plastic waste; waste treatment